2020
DOI: 10.1002/jev2.12030
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles: Natural liver‐accumulating drug delivery vehicles for the treatment of liver diseases

Abstract: Extracellular vesicles (EVs) are excellent potential vectors for the delivery of therapeutic drugs. However, issues with biological safety and disease targeting substantially limit their clinical application. EVs from red blood cells (RBC‐EVs) are potential drug delivery vehicles because of their unique biological safety. Here, we demonstrated that EVs, including RBC‐EVs, show natural liver accumulation. Mechanistically, the liver environment induces macrophages to phagocytize RBC‐EVs in a C1q‐dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 57 publications
3
100
0
Order By: Relevance
“…Extracellular vesicles (EVs) and nanovesicles (NVs) have recently been shown to have potential applications as drug carriers and may be used to overcome the limitations of cellrelated treatments (5,6,(17)(18)(19). Previous studies have shown that M1 macrophage-derived nanovesicles (M1NVs) inhibit tumor development and enhance the anti-tumor effects of programmed cell death ligand 1 (5).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) and nanovesicles (NVs) have recently been shown to have potential applications as drug carriers and may be used to overcome the limitations of cellrelated treatments (5,6,(17)(18)(19). Previous studies have shown that M1 macrophage-derived nanovesicles (M1NVs) inhibit tumor development and enhance the anti-tumor effects of programmed cell death ligand 1 (5).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes served as a nanometer biological microvesicle in transmitting various biomolecule have been characterized as a promising therapeutic target for human diseases 49–51 . Relevant studies have demonstrated the effectiveness achieved by targeting exosomal lncRNA to improve the immunotherapy and treat the metastatic peritoneal cancer, suggesting the wide application prospects of exosomal lncRNA in the treatment of tumors 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes served as a nanometer biological microvesicle in transmitting various biomolecule have been characterized as a promising therapeutic target for human diseases. 49 , 50 , 51 Relevant studies have demonstrated the effectiveness achieved by targeting exosomal lncRNA to improve the immunotherapy and treat the metastatic peritoneal cancer, suggesting the wide application prospects of exosomal lncRNA in the treatment of tumors. 52 Here, we revealed that high level of BCYRN1 in urinary‐EXO from BCa patients was associated with the LN metastasis and poor prognosis of patients, providing the clinical evidence for targeting exosomal BCYRN1 to treat LN metastatic BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Small EVs have a series of advantages as drug carriers, such as unique structure and physicochemical properties, effective cell access, low immunogenicity and toxicity, and natural capacity to cross organism barriers [ 198 , 199 ]. Additionally, MSC-derived small EVs can deliver drugs to recipient cells in a highly selective manner [ 98 , 200 ]. In other words, MSC-derived small EVs are an ideal delivery system for small molecular drugs.…”
Section: Future Perspectives Of Mensc-derived Small Evs In Regenerative Medicinementioning
confidence: 99%